2021
DOI: 10.1055/a-1497-1838
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Urinary Stress Incontinence and Levator Avulsion Detected by 3D Transperineal Ultrasound

Abstract: Purpose To determine the association between levator avulsion and urinary stress incontinence (USI) by 3/4D transperineal ultrasound. Materials and Methods 842 patients who were admitted to our hospital from 2016 to 2019 were recruited for our study. 3D/4D transperineal ultrasound was performed. After standard interview and clinical evaluation, general conditions and levator hiatus data were collected and measured to compare with each group. The odds ratio (OR) of USI symptoms or ultrasound features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
1
10
1
1
Order By: Relevance
“…The majority of prior studies regarding de novo USI have been focused on urethral obstruction or urodynamic studies, 3 with few concerned about the abnormal morphology of pelvic floor structures. In the present study, preoperative levator avulsion also seemed to be a risk factor for de novo USI after transvaginal mesh (TVM) surgery; however, no difference was found between the unilateral avulsion and bilateral avulsion group, which differs from previous studies 2 . The lack of difference between our two studied groups may be related to specific patient populations.…”
Section: Characteristic No Complication Group(n = 190) De Novo Usi Gr...contrasting
confidence: 85%
See 2 more Smart Citations
“…The majority of prior studies regarding de novo USI have been focused on urethral obstruction or urodynamic studies, 3 with few concerned about the abnormal morphology of pelvic floor structures. In the present study, preoperative levator avulsion also seemed to be a risk factor for de novo USI after transvaginal mesh (TVM) surgery; however, no difference was found between the unilateral avulsion and bilateral avulsion group, which differs from previous studies 2 . The lack of difference between our two studied groups may be related to specific patient populations.…”
Section: Characteristic No Complication Group(n = 190) De Novo Usi Gr...contrasting
confidence: 85%
“…Prior studies have suggested that between 2% and 22% of pelvic organ prolapse patients, without concurrent baseline urinary stress incontinence (USI), can develop de novo USI after vaginal surgeries 1 . In our previous study, 2 unilateral levator avulsion was shown to be a risk factor for USI. Whether levator avulsion might be a risk factor for de novo USI has not yet been reported in the existing literature.…”
Section: Characteristic No Complication Group(n = 190) De Novo Usi Gr...mentioning
confidence: 82%
See 1 more Smart Citation
“…It can also be used to specifically detect uterine abnormalities [16] or dislocations of intrauterine devices [17]. With translabial/ transperineal 3D sonography, the female pelvic floor and corresponding pelvic floor defects can be easily detected [18][19][20].…”
Section: Eberhard Merzmentioning
confidence: 99%
“…Auch können Uterusanomalien [16] oder Dislokationen von Intrauterin-Pessaren [17] damit gezielt nachgewiesen werden. Mit der translabialen/transperinealen 3D-Sonografie können der weibliche Beckenboden und auch entsprechende Beckenbodendefekte gut erkannt werden [18][19][20].…”
unclassified